2016
DOI: 10.1016/j.surg.2016.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Operative correction of abdominal rectus diastasis (ARD) reduces pain and improves abdominal wall muscle strength: A randomized, prospective trial comparing retromuscular mesh repair to double-row, self-retaining sutures

Abstract: There was no difference between the Quill technique and retromuscular mesh in the effect on abdominal wall stability, with a similar complication rate 1 year after operation. An operation improves functional ability and quality of life. Training strengthens the abdominal muscles, but patients still experience discomfort and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 32 publications
0
95
0
6
Order By: Relevance
“…Patients operated on with methods B and C had an active 14‐Fr catheter drain(s) that was removed when fluid loss was less than 50 ml/day according to local routines for ventral hernia repair. All women were instructed to wear a girdle for 12 weeks (day and night in weeks 1–8, daytime only in weeks 9–12), which has been standard (with minor adjustments) in previous studies. Patients were also instructed to participate in a standardized rehabilitation programme developed by the physiotherapy department at the authors' hospital ( Appendix S2 , supporting information), as well as daily exercise such as short walks, but to avoid heavy physical exercise during the first 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients operated on with methods B and C had an active 14‐Fr catheter drain(s) that was removed when fluid loss was less than 50 ml/day according to local routines for ventral hernia repair. All women were instructed to wear a girdle for 12 weeks (day and night in weeks 1–8, daytime only in weeks 9–12), which has been standard (with minor adjustments) in previous studies. Patients were also instructed to participate in a standardized rehabilitation programme developed by the physiotherapy department at the authors' hospital ( Appendix S2 , supporting information), as well as daily exercise such as short walks, but to avoid heavy physical exercise during the first 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…There is no strong evidence that training during pregnancy and in the postpartum period decreases the risk of persistent DRA, although some studies have reported that specific exercises could increase abdominal trunk stability and reduce some of the associated symptoms. Surgical reconstruction has been reported to restore abdominal trunk function and improve lower back pain and urinary incontinence. General awareness of symptomatic DRA is poor, and patients are commonly advised to undertake non‐specific physical training, or told that the condition is only cosmetic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The following are considered to be the risk factors of DRA: pregnancy (the resulting hormonal changes, the increased size of the uterus, anterior pelvic tilt with or without lumbar hyperlordosis, the increased intraabdominal pressure), cesarean section, multiple pregnancies, fetal macrosomia, as well as genetically-conditioned defects in collagen structure (including congenital disproportion of the collagen III/I ratio), considerable body mass losses occurring spontaneously or after bariatric surgeries, abdominal surgical procedures [2,3,11,12]. Mota et al [13] and Sperstad et al [14] reported no association between DRA and the pre-pregnancy body mass index, weight gain, a baby's birth weight or abdominal circumference, heavy lifting, lifting and carrying children, and regular exercise.…”
Section: Diastasis Recti Abdominismentioning
confidence: 99%
“…Operative repair for DRA is controversial [34]. According to Emanuelsson et al [12] the abdominal wall repair should be considered in patients with an IRD wider than 3 cm. Brauman [35] states that this decision should be influenced primarily by the evaluation of the protrusion rather than diastasis.…”
Section: Treatment Of Dramentioning
confidence: 99%
See 1 more Smart Citation